Salinity-influenced changes in the community and functional composition of zooplankton-associated bacteria in the lakes of Inner Mongolia - Li, Yuan; Wang, Qianhong; Chen, Dongyi; Liu, Xia; Chen, Feizhou (Frontiers in Microbiology, 2025)
In aquatic ecosystems, bacteria often reside on the surface or in the gut of zooplankton to play an indispensable role. Salinity is a key factor influencing the structure and functional composition of aquatic bacterial communities; however, its impact on zooplankton-associated bacteria (ZA) remains unclear. To address this knowledge gap, we conducted a study using 16S rRNA gene amplicon sequencing to investigate the ZA of the cladoceran Moina mongolica from lakes in the Inner Mongolian Plateau with different salinity groups (Low salinity: 2‰–3‰, High salinity: 17‰). By annotating the sequencing data, we identified the community structure of ZA, and we used the FAPROTAX database to infer their functional potential. Statistical analyses revealed that salinity is a significant environmental factor shaping the community structure and inferred functional composition of ZA. Higher salinity reduced the diversity and abundance of ZA, which, in turn, affected the biochemical functions contributed by these bacteria. Our results suggest that under salinity stress, the community structure and inferred functional composition of zooplankton-associated bacteria are affected, which may influence the ecological role of zooplankton in saline lakes. This study provides new insights into the ecological functions of zooplankton in saline lakes under the context of climate change and human activity.